Katera znanja bodo rabili informatiki danes in v prihodnosti - Werber, Borut (Uporabna informatika (Ljubljana), 1994)
Needed skills an knowledge of information system professionals as seen by leading IS managers and practitioners in companies and institutions are presented. Opinions of MIS managers were collected and analyzed. Dependence of the ratings from particular factors, such as their formal education, position, etc. was investigated. Results of this study were compared with the outcome of several investigations carried out in other countries.
Keywords: informacijski sistemi; innformatika; spretnosti; znanja